Spontaneous uterine rupture on uterus bicornis: a case report - Kakou, Charles F. K.; Kinifo, Yeo; Kasse, Raoul S. K.; Yao, Alexis; Akinloye, Sofia; Ampoh, Fatimata; Boni, Serge (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Uterine malformations are the most common congenital anomalies of the female reproductive system with an incidence of approximately 4%. The absence of incomplete fusion of the two Mullerian ducts leads to a bicornuate uterus. In the majority of cases, its discovery is incidental on imaging. However, an obstetric complication can be the revealing element. We report a case of spontaneous uterine rupture in a bicornis unicervical uterus at five months of pregnancy. It was a 19-year-old primigravida without prenatal follow-up. The treatment consisted of performing a hemi-hysterectomy.